The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2014
DOI: 10.3390/w6102978
|View full text |Cite
|
Sign up to set email alerts
|

Nitritation and N2O Emission in a Denitrification and Nitrification Two-Sludge System Treating High Ammonium Containing Wastewater

Abstract: Abstract:The effective management of high ammonium containing wastewater is important for the sustainable development of the wastewater industry. A pre-denitrification and post-nitrification two-sludge system was proposed to treat high ammonium containing wastewater with low carbon-to-nitrogen (C/N) ratios. In the system, pre-denitrification was adopted to use organic carbon in raw wastewater efficiently for nitrogen removal, while post-nitrification was adopted to achieve nitritation. System performance and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 40 publications
0
12
1
Order By: Relevance
“…The nitrification efficiencies did not significantly differ (P>0.05) between the high and low aeration periods, although nitrification was significantly affected by the aeration rate in an SBR process ). This inconsistency likely arises from the lower influent NH 4 + -N loading in this study than in the previous study (0.007 vs 0.289 kg N/m 3 /day; see Wu et al 2014). On the other hand, neither aeration condition significantly affected the DOC and DTN removal efficiencies (P>0.05), contradicting a previous finding that the DOC and DTN removal efficiencies depend on the aeration rates in an SBR .…”
Section: Effect Of Aeration Rates On Water Quality and N 2 O Emissionscontrasting
confidence: 51%
“…The nitrification efficiencies did not significantly differ (P>0.05) between the high and low aeration periods, although nitrification was significantly affected by the aeration rate in an SBR process ). This inconsistency likely arises from the lower influent NH 4 + -N loading in this study than in the previous study (0.007 vs 0.289 kg N/m 3 /day; see Wu et al 2014). On the other hand, neither aeration condition significantly affected the DOC and DTN removal efficiencies (P>0.05), contradicting a previous finding that the DOC and DTN removal efficiencies depend on the aeration rates in an SBR .…”
Section: Effect Of Aeration Rates On Water Quality and N 2 O Emissionscontrasting
confidence: 51%
“…Eldyasti, Nakhla, and Zhu () found that the biofilm thickness can play an important role in N 2 O emissions. Research has also investigated the potential for NO2 accumulation in nitrifying and denitrifying systems, and found that high NO2 concentration in both cases can lead to higher N 2 O emissions (Kampschreur, Temmink, Kleerebezem, Jetten, & van Loosdrecht, ; Lu & Chandran, ; Wu, Zheng, & Xing, ). However, these studies involved complex systems, in which the biofilm thicknesses, microbial composition, and substrate concentrations were not well characterized.…”
Section: Introductionmentioning
confidence: 99%
“…In the last years, many efforts have been devoted towards the understanding of the key mechanisms involved in N 2 O production and emission (Kampschreur et al, 2009;Quan et al, 2012;Rodriguez-Caballero and Pijuan, 2013;Stenstr€ om et al, 2014;Wu et al, 2014;Hwang et al, 2016;Mannina et al, 2016c). The reported studies demonstrated a huge variability of the N 2 O emission (from the 0.01% to 10% of the influent total nitrogen) (Yoshida et al, 2014), depending on the WWTPs operational conditions (Kampschreur et al, 2009;Law et al, 2012;Daelman et al, 2013).…”
Section: Introductionmentioning
confidence: 99%